Development and application of differential scanning calorimetry for monitoring and assessing various quality parameters in palm oil. - Che Man, Yaakob; Tan, C. P. (2001)
Today, differential scanning calorimetry (DSC) is used in Virtually every area of modern science and technology. In the field of oils and fats, the thermal behavior of edible oils and fats continues to be an interesting subject of active research and debate. These thermal behaviors are fundamental subjects to elucidate the oils and fats physical and chemical properties. The versatility of DSC has been demonstrated in this work. In this study, a number of different palm all products have been characterized in term of their thermal properties. Thorough investigations were also directed towards obtaining basic information about the relationship between thermal profile and chemical composition of these oil products. In another study, a simple and reliable DSC method was developed for monitoring the oxidation of frying oils. The study revealed that the DSC could be a reliable and effiCient alternative to existing methods for monitoring the extent of lipid oxidation in palm oil. Recently, we have developed new colorimetric techniques for determining three important quality indices in deep-fat frying industry namely, total polar compounds (TPC), free fatty acid (FFA) content, and iodine value (IV) of heated RBD palm olein using the DSC thermal profiles. The studies have shown that all DSC methods developed were comparable to the standard American Oil Chemists'Society (AOCS) methods. We also developed a new method for measuring the antioxidant activity in RBD palm olein (RBDPOo) using DSC. The results indicated that DSC is a valuable technique in the development and optimization of antioxidant system for RBD palm olein. Furthermore, the isothermal DSC method was applied to obtain the kinetic data for lipid oxidation of RBDPO. These observations strengthen the premise that DSC is an efficient and accurate method for analyzing palm oil products. It could be used for routine analysis In the palm oil Industry. In oddition, the DSC method offers an alternative for the analysis of palm oil products due to its appreciable time-saving, small samples with minimal preparation and free of toxic chemicals usage.